Dimensional changes of hard and soft tissue after immediate implantation in comparison with conventional tooth extraction (Bangladesh Journal of Medical Science, 2016)
Introduction: Immediate implantation in single-root teeth has been claimed to possess some benefits, especially bone preservation. The aim of this study was to evaluate ridge changes after immediate implantation in comparison with tooth extraction and dental socket healing.Methods and Materials: In this study, 21 patients with hopeless single-root teeth were selected. After impression and cast making, the patients were divided into test and control groups. Each group included twelve dental sockets. For all teeth the extraction was performed atraumatically. Measurements included bucco-lingual ridge dimensions at 3mm and 7mm apical to an imaginary line connecting the CEJs of the two adjacent teeth (CEJ line) as well as vertical distance between the mentioned line and bone crest at the misobuccal, midbuccal, distobuccal, mesiopalatal, midpalatal, and distopalatal aspects. In addition, soft tissue measurements similar to hard tissue ones were taken using stone casts and acrylic stents. In test group immediate implantation was carried out following extraction whereas in the control group dental sockets were left for natural healing. Four months after the operation, in both groups, the flap was reflected and measurements taken at baseline were repeated.Results: Vertical changes of soft tissues in test group were significantly less than control group at all points except in mid-buccal aspect (p=0.033 for mesiobuccal, p=0.026 for distobuccal, p=0.004 for midpalatal, p=0.002 mesiopalatal, p=0.022 for distopalatal, p=0.016 for distal, p=0.048 for mesial). Horizontal dimension change of soft tissue at 7mm apical to the CEJ line in test group, were also significantly less than control group (p= 0.051). Vertical changes of hard tissue, measured in all points, in test group were less than those of control group. These changes were significant in mid-buccal, mid-palatal, mesiopalatal and distopalatal points (p= 0.046, 0.029, 0.020 and 0.026 respectively). Horizontal changes of hard tissue at 3mm and 7mm apical to the CEJ line in test group were also less than control group. However, this was significant only at the 3mm point (p=0.028).Conclusion: According to the results of this study, it can be concluded that immediate implantation is to some extent effective in reducing the expected vertical and horizontal bone and soft tissue changes occurring following conventional tooth extraction and natural socket healing. Further investigation is warranted to determine the optimum method of preventing these changes.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.335-342